内蒙古早二叠世构造古地理的再造 - 邵济安; 唐克东; 何国琦 (岩石学报, 2014)
针对近年来关于内蒙古中部早二叠世古亚洲洋存在和向南北两侧大陆俯冲的观点,本文通过构造古地理图的编制,结合早二叠世沉积岩相、古地理、生物组合、陆源碎屑以及烃源岩的讨论,认为中亚陆块和华北克拉通之间晚古生代存在的是陆壳基底之上发育的陆表海和裂陷槽,而不是大开大合的大洋。我们的研究揭示了该区的演化过程。早二叠世早期伴有强烈火山喷发的沉积作用受到三条近东西向分布的同沉积裂陷槽的控制,由北向南,其滨-浅海相的沉积-火山岩厚度分别>8000m;>5000m和2900m,显示基底为不稳定的裂陷槽。沉积作用受到深断层控制的观点得到本区深部地球物理探测资料的佐证。早二叠世早期沉积岩以粗碎屑岩为主,其中成熟度低的. In contrast of the recently promoted view of point that there was a Paleo-Asian Ocean plate subducting towards the continents on its north and south sides in the Early Permian, the present authors prefer a different understanding. Through compilation of a tectono-palaeogeographic map of the concerned area based on all the facts about the sedimentary petrography, palaeogeography, biologic association, detrital materials of terrigenous origin, and hydrocarbon source rock in the Early Permian, it seems to the authors that what existed between the Central Asian massif and the North China Craton was a Late Paleozoic epicontinental sea and rift instead of a large-scale ocean experiencing spreading and closure. Our studies reveal the actual evolution of the concerned area in the Early Permian. In the early stage, the sedimentary process accompanying strong eruption of basic-acidic volcanic rocks is controlled by three syn-sedimentary rifts with near EW strike, with the thicknesses of sedimentary rocks of the littoral-shallow marine facies and volcanic rocks being >8000m, >5000m, and 2900m separately from north to south. The view point of sedimentation being controlled by deep faults is supported by the deep geophysical data. The sedimental rocks of the early stage are mainly consisted of coarse clastic rocks in which the greywackes and arkoses with lower maturity are distributed widely. Besides, the denudation areas are composed of neogenic continental crusts and the proximal sediments are characterized by quick-accumulation, as seen from compositions and origins of the terrigenous detrital materials. In the later stage, the sedimentary rocks appear as grey blocks of carbonaceous siltstone and slates interlaced with limestone lenses, in which the dark marine mudstones with increased organic abundance form hydrocarbon source rocks R-0 = 1.01% similar to 3.67%) in prodeltas, shallow seas, and bathyal regions. The resulted sedimentary association reflect processes in which maturity of the continental crust become increased, the tectonic activities declined, and the epicontinental sea shrined. The Early Permian palaeocoenosis is mainly consisted of Brachiopods, corals, fusulinidss and bryozoan formed in a littoral-shallow sea environment, among which the corals can only live in clear and warm littoral-shallow seas just outside the low-water lines and not deeper than 50 meters. Occurrence of phytoclasts also reflects the settings being paralic facies. By the end of the Early Permian, the palaeocoenos has become mixotrophic, with its main part consisted of the kind of the Arctic region such as Spiriferella everywhere and mixed with such elements of polytherm as Richtofenia, Enteletes, etc. Such a phenomenon indicates that collision of the two plates has already occurred before and no ocean basin exists in the Early Permian. Radiolarians could not be as the definite evidence of existence of an ocean crust because radiolarians may exist in waters of different depths, as shown by coexistence of fossils of the radiolarians, ammonoites, gastropods, bivalves, and even plants in the Zhesi Formation in Maodeng area. The magmatism of the area is featured as that the bimodal volcanic rocks of the Early Permian Dashizhai Formation (281 similar to 270Ma) have their basaltic magma coming from a depleted mantle and mixed with crustal matters when uplifting (I-Sr = 0.7024 similar to 0.7069, epsilon(Nd) (t) = -3.6 similar to + 7. 9), and that the synchronous alkaline granites and large basic dykes (299 similar to 263Ma) are distributed in large grabens as belts, and have Sr-Nd isotopic features of mantle source rocks: epsilon(Nd)(t) = 3.0 similar to 5.4, I-Sr = 0. 7053 similar to 0.7088, epsilon(Hf)(t) = -2.7 similar to 2.4. The regional tectonic evolution of the area is characterized by that its magmatism is consistent with that of the synmagmatic rifting type (bimodal volcanic rocks and peralkalic plutonic rocks) in Mongolia, belonging to magmatism controlled by rifts in extending settings rather than one related with subduction in a compressive regime. The Late Palaeozoic Baolige rift in the concerned area is connected with Gebi-Tianshan rift in southern Mongolia to consistent so large-thousands of kilometers-a continental rift, clearly showing that the Central-Asia orogenic zone has already entered a new continental-crust evolution stage since Carboniferous-Permian under the extended tectonic setting. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000339456100002&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 SCI(E) 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 7 wangcc@tsinghua.edu.cn 07 1858-1866 30